PENGARUH IMPLEMENTASI GOOD CORPORATE GOVERNANCE, KOMPETENSI AUDITOR INTERNAL DAN EFEKTIVITAS PENGENDALIAN INTERNAL TERHADAP KECURANGAN PRAKTIK PERBANKAN DENGAN WHISTLEBLOWING SYSTEM SEBAGAI VARIABEL MODERASI: Studi Kasus PT Bank Mandiri (Persero) Tbk Area Pluit Selatan Jakarta Utara - Siti Rahma Yanti; Nurul Hidayah (Politeknik Ganesha Medan, 2023)
The purpose of this study aims to examine the variables implementation of good corporate governance, internal auditor competence and the effectiveness of internal control influences fraudulent banking practices with the whistleblowing system as a moderating variable. The population in this study consists of employees at the manager, officer, and supervisor level at PT Bank Mandiri (Persero) Tbk, South Pluit Area, North Jakarta. The sampling method used is simple sensus sampling. In this research, the total sample is 83 respondents. The type of data used was primary data obtained from the results of questionnaire answers by sample. The smart Partial Least Square (SmartPLS) path modelling method is used as an analysis method. The results of this study indicate that the competence of internal auditors and the effectiveness of internal controls significantly affect fraudulent banking practices. Meanwhile, implementing good corporate governance has no significant effect on fraudulent banking practices. Then the results of this study indicate that the whistleblowing system can moderate the influence of the competence of internal auditors and the effectiveness of internal controls on fraudulent banking practices. However, the whistleblowing system has not been able to moderate the effect of implementing good corporate governance on fraudulent banking practices.